Is There a Positive Side to T Cell Exhaustion? - Pawelec, Graham (Frontiers in Immunology, 2019)
T cell “exhaustion” describes a state of late-stage differentiation usually associated with active prevention of functionality via ligation of negative signaling receptors on the cell surface, and which can be reversed by blocking these interactions. This contrasts with T cell “senescence,” which has been defined as a state that is maintained by intrinsic internal cell signaling (caused by DNA damage or other stresses) and which can be reversed pharmacologically. Interventions to alleviate these two different categories of inhibitory pathways may be desirable in immunotherapy for cancer and possibly certain infectious diseases, but reciprocally inducing and maintaining these states, or some properties thereof, may be beneficial in organ transplantation and autoimmunity. Even under physiological non-pathological conditions, T cell exhaustion and senescence may play a role in the retention of T cell clones required for immunosurveillance, and prevent their loss via elimination at the Hayflick limit. This essay briefly reviews T cell exhaustion in contrast to replicative senescence, and circumstances under which their modulation may be beneficial.